Integrated Renewable Energy System Using High Gain Interleaved Boost Converter with Modified Cheetah Optimization Based Adaptive PI-Controller - Sharda P.; Himanshu S.; Pal R. K. (Problems of the Regional Energetics, 2025)
This study introduces an innovative strategy to boost the uptake of Electric Vehicles (EVs) while curbing greenhouse gas emissions. Addressing the primary limitation of EVs - their reliance on energy storage - entails integrating a high-performance brushless DC (BLDC) motor renowned for its swift dynamic response and efficiency. The main objective of the study is to merge Photovoltaic (PV) energy generation with a bidirectional grid connection for powering the BLDC motor effectively. This objective is achieved by the introduction of a High Gain Interleaved Boost Converter (HGIBC) for enhancing voltage-gain ratio and system adaptability of the PV system. A novel Modified Cheetah Optimization (MCO)-based Proportional Integral (PI) controller ensures precise control signal generation for the converter. The AC supply to the motor is facilitated by a 3-phase Voltage Source Inverter (VSI), with speed regulation achieved through a PI controller. Simultaneously, the Bidirectional single phase grid augmented with an adaptive PI controller and a battery system with bidirectional converter distribute power supply to the BLDC motor fed EV during in sufficient power supply from PV system due to its ecological changes. Moreover, to validate the importance of proposed system, MATLAB/Simulink is utilized. The most important results are the proposed HGIBC exhibits a higher voltage gain when compared to other existing Boost converters and generates an increased efficiency of 97%. Also, with the optimized PI controller a steady converter output of 1000V is achieved at 0.35s which indicates a reduced settling time. Also, the proposed work generates a reduced simulation THD value of 1.21%. The significance of the obtained results lies in the delivering of high converter efficiency, improved power quality and reliable performance of BLDC motor system.